DIAGNÓSTICO FINANCIERO Y PROPUESTA DE MEJORAS PARA LA COOPERATIVA DE AHORRO Y CRÉDITO ECONOMÍA DEL SUR ECOSUR DEL CANTÓN SARAGURO, PERÍODO 2016-2017 - Paredes Arrobo, Lucy Estefanía (2019)
The present thesis work entitled: "FINANCIAL DIAGNOSIS AND PROPOSAL OF IMPROVEMENTS FOR THE SAVING AND CREDIT COOPERATIVE ECONOMY OF THE SOUTH ECOSUR OF THE SARAGURO SONG. PERIOD 2016 - 2017" was carried out in order to determine the real economic-financial situation of the cooperative and thus be able to establish possible solutions to the problems encountered in a way that allows its directors to make better decisions. The methodology used in the development of the financial diagnosis begins with the compilation of fundamental information for its development, such as the financial statements and complementary data of the cooperative, then proceeded to comply with the specific objectives established, starting with the application of the situational analysis, where internal and external factors were evaluated, thereby determining strengths, weaknesses, opportunities and threats, and at the same time was prepared the EFE and EFI matrices obtaining weighted averages that indicated that the cooperative is taking advantage of the opportunities, however, has a weak internal position. Also, the SWOT matrix with their respective strategies was elaborated. Next, a vertical analysis of the financial statements was carried out in order to know the economic-financial structure of the cooperative. Where the most representative accounts were determined, with respect to Assets, 65.31% corresponds to the credit portfolio, Liabilities, 80.59% in obligations with the public and Equity, 19.19% in the social capital. While in income the account with greater relevance was interest and discounts earned with 76.15% of total income and in expenses was the account operating expenses with 61.58% in relation to total expenses, providing a surplus, which contributed to cover a percentage of the accumulated losses of the cooperative in previous years. Similarly, horizontal analysis was applied to identify the variations existing between 2016-2017, resulting in a high growth in assets of 70.39%, specifically in available funds increased by 710.58%, in liabilities of 89.66%, an increase of 330 was evidenced,81% in accounts payable and in total equity 16.64%, with an increase in reserves of 37.81% while revenues increased 25.95%, where the income from services account increased by 56.10% and expenses by 23.71% with an increase in the interest account caused by 27.12% generating a surplus at the end of the year. 5 In addition, with the application of the financial indicators proposed by the PERLAS Monitoring System, it became evident that the institution has an optimal growth of fixed-term deposits, it has the necessary liquidity to assume the withdrawal of money captured at any time, however, it is excessive. It also has weak institutional capital, high levels of delinquencies, unproductive assets, unproductive liquid assets and high operating expenses. Finally, the weak areas of the cooperative were identified by formulating solutions through the proposal of improvements based on the strategies obtained from the situational analysis. Subsequently, a report is attached for consideration by the directors of the entity to improve decision-making and the application of corrective measures.